2008
DOI: 10.1093/fampra/cmn008
|View full text |Cite
|
Sign up to set email alerts
|

Effects on readiness to change of an educational intervention on depressive disorders for general physicians in primary care based on a modified Prochaska model--a randomized controlled study

Abstract: Educational formats that suit different stages of learning can support primary care doctors to reach higher stages of behavioural change in the topic of depressive disorders. Our findings have practical implications for conducting CME programmes in Iran and are possibly also applicable in other parts of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…26 These results add to the growing evidence to support clinician education based on readiness to change. [22][23][24] The findings are similar to those of Shirazi and colleagues, 24 who reported that education tailored to different stages of readiness to address depression in primary care enabled clinicians to move to more advanced stages of readiness, and the findings of Johnson et al 26 who reported that TTM-based CME for specialists increased readiness to employ best practices in individualizing early and aggressive treatment of rheumatoid arthritis. The appeal of this type of approach to improve clinical practice is enhanced when one considers how cost-effectively online CME can be provided and the convenience if offers clinicians.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…26 These results add to the growing evidence to support clinician education based on readiness to change. [22][23][24] The findings are similar to those of Shirazi and colleagues, 24 who reported that education tailored to different stages of readiness to address depression in primary care enabled clinicians to move to more advanced stages of readiness, and the findings of Johnson et al 26 who reported that TTM-based CME for specialists increased readiness to employ best practices in individualizing early and aggressive treatment of rheumatoid arthritis. The appeal of this type of approach to improve clinical practice is enhanced when one considers how cost-effectively online CME can be provided and the convenience if offers clinicians.…”
Section: Discussionsupporting
confidence: 74%
“…20,21 Tailoring educational content to readiness to adopt a performance change is also likely to play a key role. [22][23][24][25] The Transtheoretical Model (TTM) is an integrative model that describes behavior change as a progression through a series of five stages of readiness: (1) Precontemplation: not intending to adopt the best practices, (2) Contemplation: intending to adopt the best practices in the next six months, (3) Preparation: intending to adopt the best practices in the next 30 days, (4) Action: adopted the best practices less than six months ago, and (5) Maintenance: adopted the best practices more than six months ago. The TTM could provide a useful framework for tailoring CME content in that leveraging the principles of the TTM permits the inclusion of behavior change statements to ensure activities meet the needs of all physicians, even those who are not prepared to adopt the desired performance.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…The 192 GPs were first grouped according to their expressed stages of readiness to change and stratified based on gender, age, and length of work experience (three levels) [20]. Thereafter, they were randomly allocated within each subgroup to the intervention ( n = 96) or the control arm ( n = 96).…”
Section: Methodsmentioning
confidence: 99%
“…The content stressed recognition and diagnosis rather than treatment. The trans ‐theoretical model postulates that physicians who already are in the intention stage of change should be given material and specific educational formats that emphasize practical treatment strategies and clarification of differential diagnoses, because they are ready to accept this [20]. Therefore, as GPs in the small intervention group were all in the intention stage, they participated in a workshop setting, mainly using case illustrations presented through SPs, role playing, cooperative learning techniques (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Two important personal attributes - self-efficacy and readiness to change - have been associated with health behavior change in patients and to a lesser extent to use of guidelines by clinicians 1720 . Self-efficacy, (the degree of confidence in one’s capacity for success in implementing a goal-directed behavior 21 ), is a personal attribute that is central to social learning theory (SLT) 22 .…”
Section: Introductionmentioning
confidence: 99%